Interface truth material with prohibition of use of the results of the aircraft accident ivestisation as a tool of evidence - Muchtadin Al attas (Indonesia Prime, 2019)
Ratio legis of Article 359 of the aviation law (number 1 of 2009) is results of the investigation is not made for the judicial system but rather aims of improving flight safety and prevent accidents with the same cause. Validating the material truth in aircraft accidents can still be achieved, although the results of the investigation can not use as evidence